Campus Promotion Management in the Context of Increasing Public Animo Entering the Campus of Al-Muslim Bireun University Aceh - Marsitah, Iis; Husna, Milda; Maharani, Maharani; Humairah, Humairah; Andani, Andani (Jurnal Pendidikan Indonesia, 2023)
This study aims to determine campus promotion management in order to increase public interest in entering the Al-Muslim Bireun Aceh University campus. This type of research is qualitative research. This research was carried out at Al-Muslim University because this campus is a private campus that must be active in carrying out a campus promotion, in order to increase public interest in order to enter the Al-Muslim University campus. This data collection method is done by interview, documentation, and observation. The data analysis in this study uses the data triamulation method, which is a method by exploring the truth of information by exploring the truth of information from various sources and conducting interviews with more than one source who has different views. Based on the results of the data analysis, the following conclusions can be drawn: (1) Campus promotion management in order to increase community anime entering Al-Muslim university campuses is quite optimal, both in planning, organizing, implementing and supervising. (2) Supporting factors include: the support of quality human resources and the existence of various campus advantages, the existence of adequate facilities and infrastructure, and the existence of several services available on campus, such as Bidikmisi, Kip-Kuliah, Aceh Carong, and other scholarships. (3) Public interest with the promotion management of the Al-Muslim Bireun Aceh University campus is getting better. the support of quality human resources and the existence of various campus advantages, the existence of adequate facilities and infrastructure, and the existence of several services available on campus, such as bidikmisi, Kip-Kuliah, Aceh Carong, and other scholarships. (3) Public interest with the promotion management of the Al-Muslim Bireun Aceh University campus is getting better. the support of quality human resources and the existence of various campus advantages, the existence of adequate facilities and infrastructure, and the existence of several services available on campus, such as bidikmisi, Kip-Kuliah, Aceh Carong, and other scholarships. (3) Public interest with the promotion management of the Al-Muslim Bireun Aceh University campus is getting better.